Revitalizing Spirituality through Socio-Sufism: M. Fethullah Gülen's Integration of Sufi Ethics and Social Engagement - Aisyah Nur; Gazali (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2026)
The marginalization of religious values amid secularization, materialism, and individualism has generated a need for forms of spirituality that address not only inner transformation but also contemporary social responsibility. While modern discussions of Islamic spirituality often emphasize individual piety and mystical experience, the social and ethical dimensions of Sufi spirituality remain comparatively underexplored. This article examines M. Fethullah Gülen's conception of socio-Sufism as a framework that integrates Sufi ethics with social engagement. It aims to analyze the conceptual foundations of Gülen's socio-Sufism, examine how spiritual cultivation is translated into social responsibility, and assess its relevance to the revitalization of spirituality in modern society. Employing qualitative library research with philosophical and historical-contextual approaches, the study analyzes Gülen’s major works and relevant scholarly literature through qualitative content analysis. The findings demonstrate that Gülen's socio-Sufism is structured through the dynamic relationship between tazkiyah al-nafs as inner spiritual formation, hizmet as the ethical expression of spirituality through service, and collective social praxis as the broader realization of spiritual values. This integration transforms Sufism from an exclusively inward-oriented spiritual practice into an ethically engaged mode of religious life in which personal piety and social responsibility are mutually reinforcing. The study concludes that Gülen's socio-Sufism provides a relevant conceptual framework for revitalizing spirituality by reconnecting inner moral transformation with social engagement and ethical responsibility in modern society.